Pengaruh Customer Relationship Management terhadap Kepuasan dan Loyalitas Pelanggan Resto Padang di Kota Palembang - Rully Armanto; Muji Gunarto; Rama Waluyo (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of CRM on customer satisfaction, the effect of CRM on customer loyalty, and the effect of customer satisfaction on customer loyalty at Resto Padang in Palembang City. As many as 100 customers obtained the quantitative research method by sampling using the Slovin formula. The analysis technique uses Partial Least Square (PLS). The results of the CRM study had a significant effect on Consumer Satisfaction counting (24,037) > t-table (1.96) with P-Values (0.000) values < 0.05. The customer satisfaction statistical test results significantly affect customer loyalty (t-value=8,459) > t-table=1,984). The CRM statistical test does not significantly affect customer loyalty. This is clearly seen with the calculation result (0.296) < t-table (1.96) with P-Values (0.767) > 0.05. Consumer satisfaction statistics test significantly affects customer loyalty.